A method of determining and visualizing safe motion parameters of a ship navigating in restricted waters. (1st January 2017) - Szlapczynski, Rafal; Szlapczynska, Joanna
Abstract: The paper presents a method of displaying ship collision avoidance information which is based on an unconventional Collision Threat Parameters Area (CTPA) technique. The solution presented here extends CTPA's functionality from past works by supporting navigation in restricted waters and handling ship domains analytically instead of numerically. It visualizes potential navigational threats as well as possible collision avoidance manoeuvres. The proposed method provides three types of information: targets' motion parameters (typical for target tracking), combinations of own course and speed which collide with those targets (typical for CTPA displays) and combinations of own course and speed which collide with stationary obstacles (new elements). Optionally it is also possible to display only manoeuvres compliant with International Regulations for Preventing Collisions at Sea (COLREGS) for the present visibility conditions. A superposition of all these types of data enables a navigator to quickly choose an efficient collision avoidance manoeuvre. The paper includes a description of the proposed visualization technique as well as examples of visualised data for encounter situations, which demonstrate the proposed method's usefulness. Highlights: An unconventional method of determining and presenting ship collision avoidance manoeuvres is proposed. The method returns and displays all safe combinations of own course and speed. Ship's motion parameters colliding with targets or stationary obstacles are marked so as to be avoided. Targets' elliptic domains are handled analytically for better computational time. A superposition of the presented data enables a navigator to choose a safe manoeuvre quickly. The unique advantages of the method are discussed over a variety of example scenarios.